Is "Kulturnation" a Synonym for "National Identity"? - Helmut Peitsch (Studies in 20th & 21st Century Literature, 2002)
Literature and German Unification by Stephen Brockmann is a pioneering study, even if I am not as sure as the dust cover writer if it constitutes "the first systematic attempt in English to examine the literary consequences of German reunification." Stephan...
Keywords: Literature and German Unification; Stephen Brockmann; German reunification; Germany; reunification; Kulturnation